Delta-9-Tetrahydrocannabinol Blocks Bone Marrow-Derived Macrophage Differentiation through Elimination of Reactive Oxygen Species - Taylor H. Carter; Chloe E. Weyer-Nichols; Jeffrey I. Garcia-Sanchez; Kiesha Wilson; Prakash Nagarkatti; Mitzi Nagarkatti (MDPI AG, 2024)
Macrophages are vital components of the immune system and serve as the first line of defense against pathogens. Macrophage colony-stimulating factor (M-CSF) induces macrophage differentiation from bone marrow-derived cells (BMDCs). Δ9-tetrahydrocannabiol (THC), a phytocannabinoid from the Cannabis plant, has profound anti-inflammatory properties with significant effects on myeloid cells. To investigate the effect of THC on macrophage differentiation, we cultured BMDCs with M-CSF in the presence of THC. Interestingly, THC markedly blocked the differentiation of BMDCs into CD45 + CD11b + F4/80+ macrophages. The effect of THC was independent of cannabinoid receptors CB1, and CB2, as well as other potential receptors such as GPR18, GPR55, and Adenosine 2A Receptor. RNA-seq analysis revealed that the THC-treated BMDCs displayed a significant increase in the expression of NRF2-ARE-related genes. KEGG pathway analysis revealed that the expression profiles of THC-treated cells correlated with ferroptosis and glutathione metabolism pathways. Fluorescence-based labile iron assays showed that the THC-treated BMDCs had significantly increased iron levels. Finally, THC-exposed BMDCs showed decreased levels of intracellular ROS. THC has the unique molecular property to block the Fenton Reaction, thus preventing the increase in intracellular ROS that is normally induced by high iron levels. Together, these studies demonstrated that THC blocks M-CSF-induced macrophage differentiation by inhibiting ROS production through both the induction of NRF2-ARE-related gene expression and the prevention of ROS formation via the Fenton Reaction.